1997
DOI: 10.1074/jbc.272.11.7464
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Protein Kinase C, Ras, and Raf-1 Kinase on the Induction of the Cardiac B-type Natriuretic Peptide Gene through a Critical Promoter-proximal M-CAT Element

Abstract: The cardiac genes for the A-and B-type natriuretic peptides (ANP and BNP) are coordinately induced by growth promoters, such as ␣ 1 -adrenergic receptor agonists (e.g. phenylephrine (PE)). Although inducible elements in the ANP gene have been identified, responsible elements in the BNP gene are unknown. In this study, reporter constructs transfected into neonatal rat ventricular myocytes showed that in the context of 2.5 kilobase pairs of native BNP 5-flanking sequences, a 2-base pair mutation in a promoter-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 70 publications
1
35
0
Order By: Relevance
“…Cell Culture-Primary ventricular myocytes, prepared from 1-4-day-old neonatal rats as described previously (9,15,17), were transfected (see below), plated onto fibronectin-coated plastic dishes, and then maintained for about 18 h in DMEM, 10% fetal bovine serum. The cultures were then washed briefly with medium, refed with serum-free, hormone-free DMEM containing 1 mg/ml bovine serum albumin, maintained for an additional 48 h and then extracted for reporter enzyme assays.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cell Culture-Primary ventricular myocytes, prepared from 1-4-day-old neonatal rats as described previously (9,15,17), were transfected (see below), plated onto fibronectin-coated plastic dishes, and then maintained for about 18 h in DMEM, 10% fetal bovine serum. The cultures were then washed briefly with medium, refed with serum-free, hormone-free DMEM containing 1 mg/ml bovine serum albumin, maintained for an additional 48 h and then extracted for reporter enzyme assays.…”
Section: Methodsmentioning
confidence: 99%
“…Transfections-After isolation, myocardial cells were resuspended at a density of 30 million cells/ml minimal medium (DMEM (Sigma) containing 1 mg/ml bovine serum albumin) and transfections were carried out as described previously (9,15,17). Briefly, for each transfection, 300 l, or 9 million cells, were mixed with 15 to 30 g of a reporter construct (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to GATA4, a number of other transcriptional regulators, such as nuclear factor of activated T‐cells (NFAT), NKX‐2.5, Elk‐1, activator protein 1, myocardin, serum response factor, and nuclear factor kappa B, have been shown to participate in transcriptional regulation of BNP 20, 27, 28, 29, 30, 31, 32. Several studies have also indicated a central role for M‐CAT element, a thyroid‐responsive element and shear stress‐responsive element on the BNP promoter regulating BNP transcriptional activity 33, 34, 35, 36. In conclusion, the factors regulating cardiac hypertrophy, mainly MAPKs and GATA4 transcription factor activity, are also associated with regulation of NP expression levels.…”
Section: Regulation Of Anp and Bnp Gene Expressionmentioning
confidence: 99%